A cross-sectional observational study of suicidal behavior among people in prison at Lajpore Central district jail, India - Patel, Dhaval J (The journal of forensic psychiatry & psychology, 2025)
Suicidal ideation assessment can help reduce the suicide rate among people in prison. Studies for the assessment of suicidal ideation and risk factors for suicide among inmates have been done in Western countries, but in India, data is lacking regarding the assessment of suicidal ideation among the people in prison. 1. To assess the prevalence of suicidal ideationin people in prison. 2. To identify aggravating factors for suicidal behavior. It was a cross Sectional Observational Study at a district jail, Lajpore, Surat, Gujarat. After permission from the jail authority, people in prison with or without conviction, who were willing to give consent for participation, were enrolled in the study. Semi-structured questionnaires are used to assess socio-demographic profiles. Modified Suicide Ideation scale (MSSI) and General Health Questionnaire (GHQ) and PatientHealth Questionnaire (PHQ) scales were used as materials to assess suicidal ideation and psychiatric comorbidity. Frequency analysis and Pearson correlation among various factors with the use of appropriate statistical methods. Descriptive and qualitative analysis of data was done on 140 incarcerated persons in prison. Analysis showed that 10 (7.1%) people in prison had moderate suicidal ideation in the last 48 hours while 58 (41.4%) people in prison had suicidal ideation at any point in their life. The prevalence of depressive symptoms was high among people in prison. 57.9% had minimal depressive symptoms, while 9.3% had moderate to severe symptoms. Non-convicted inmates from urban areas were having significantly more psychological distress and depressive symptoms than other inmates. Advanced ageof the inmates, negative impact of imprisonment on life, depressive symptoms, and psychosocial distress emerged as risk factors correlated with suicidal ideation. During suicide risk assessment, inmate’s age, the impact of imprisonment, psychosocial distress, and depressive symptoms should be considered as risk factors among people in prison.